Analisis Literatur Tentang Fisika Zat Padat Dalam Pegembangan Teknologi Semikonduktor - Telaumbanua, Sabar April Aman; Telaumbanua, Jefrin (CV. SINAR HOWUHOWU, 2025)
This study analyzes the literature on solid-state physics and its contributions to the development of semiconductor technology. Solid-state physics examines the properties and behaviors of materials in the solid phase, which is crucial for understanding electronic phenomena within semiconductors. The aim of this research is to explore various models and theories that explain material characteristics, including free electron theory and crystal structure, as well as their applications in semiconductor devices such as transistors and diodes. The method employed is a literature review of relevant sources. The analysis results indicate that a deep understanding of crystal structure and electrical properties of materials can enhance efficiency and innovation in semiconductor technology. This study also highlights the importance of the interaction between solid-state physics theory and material engineering practices in creating better semiconductor devices. The conclusion of this research is that solid-state physics plays a key role in the development of semiconductor technology, and the integration of theory with practical applications is essential to drive further innovations in this field.